SIFO 1988: General public and private motorism - Swedish Institute of Public Opinion Research; Dagens Nyheter (Swedish Institute of Public Opinion Research, 1993)
The Swedish Institute of Public Opinion Research (SIFO) carried out this survey at the request of the daily paper Dagens Nyheter. Questions were asked about the household's use of and dependence on cars. For what purpose is the car used. Distance travelled annually because of journeys to work, errands and recreation. Is the car used to leave and fetch children at day-care centre in connection with journeys to work. Should politicians make it easier for motorists. Readiness to pay more taxes to get a better road network. Use of public transportation because it is more environmentally sound. What car producers ought to concentrate on. How to collect information when to purchase a car. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1985.

The Swedish Institute of Public Opinion Research (SIFO) carried out this survey at the request of the daily paper Dagens Nyheter. Questions were asked about the household's use of and dependence on cars. For what purpose is the car used. Distance travelled annually because of journeys to work, errands and recreation. Is the car used to leave and fetch children at day-care centre in connection with journeys to work. Should politicians make it easier for motorists. Readiness to pay more taxes to get a better road network. Use of public transportation because it is more environmentally sound. What car producers ought to concentrate on. How to collect information when to purchase a car. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1985.
SIFO 1988: Allmänheten och privatbilismen
Keywords: TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap